National-cultural peculiarity of toponyms in proverbs that denote man’s features of character (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with toponyms which are represented in Ukrainian proverbs that denote man’s features of character; the mechanism of rendering of emotional-expressive attitude of the people towards places that have certain proper names is described. It is proved on the concrete illustrated material that toponyms in proverbs preserve generalized designation of features of character which are specific for a geographical object.
Keywords: toponym; hydronym; features of character; positive evaluation; negative evaluation